2020
DOI: 10.1186/s12935-020-1109-2
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 7 is a drug-able target that promotes hepatocellular carcinoma and chemoresistance

Abstract: Background: Ubiquitin-specific protease 7 (USP7) is a de-ubiquitin enzyme that plays an essential role in multiple cancers and becomes a target for treatment. However, the role of USP7 and its therapeutic value for HCC remains unclear. Methods: USP7 expression was examined in HCC tissues by western blot and immunohistochemistry. The correlation of USP7 and HCC prognosis was analyzed by Kaplan-Meier survival method. Mass spectrometry was determined and cell proliferation and tumorigenicity assays were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Enthusiasm for this approach is demonstrated by the dozens of small molecule USP7 inhibitors developed in the past few years. While human trials of USP7 inhibitors have yet to be conducted, many of these compounds have been found to inhibit cancer cell growth in vitro , as well as in animal xenograft models ( Fan et al, 2013 ; Agathanggelou et al, 2017 ; Turnbull et al, 2017 ; Peng et al, 2019 ; Zhang et al, 2020 ). The molecular basis of the interaction between several inhibitors and USP7 has been determined, revealing that these small molecules largely target the USP7 catalytic domain [ Figure 4 and Table 2 ; for a recent and extensive review, see Li and Liu (2020) ].…”
Section: Usp7: Links With Cancermentioning
confidence: 99%
“…Enthusiasm for this approach is demonstrated by the dozens of small molecule USP7 inhibitors developed in the past few years. While human trials of USP7 inhibitors have yet to be conducted, many of these compounds have been found to inhibit cancer cell growth in vitro , as well as in animal xenograft models ( Fan et al, 2013 ; Agathanggelou et al, 2017 ; Turnbull et al, 2017 ; Peng et al, 2019 ; Zhang et al, 2020 ). The molecular basis of the interaction between several inhibitors and USP7 has been determined, revealing that these small molecules largely target the USP7 catalytic domain [ Figure 4 and Table 2 ; for a recent and extensive review, see Li and Liu (2020) ].…”
Section: Usp7: Links With Cancermentioning
confidence: 99%
“…Of them, through deubiquitinating a wide range of substrates, USPs family members are involved in various physiological and pathological processes. Our previous study has suggested USP7 as a drug-able target that promoted chemoresistance of HCC (8). Recently, increasing studies indicate that USPs are implicated in the progression of HCC.…”
Section: Introductionmentioning
confidence: 98%
“…For example, USP7 promotes intrinsic apoptosis through p53, SUV39H1, and PLK1 and suppresses intrinsic apoptosis through MDM2 and Maf and suppresses the ER stress response. In addition, USP7 promotes extrinsic apoptosis by promoting RIPK1 activity and ferroptosis by suppressing SCL7A11 expression (Figure 3a) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. BAP1 provides another example of the complex regulation of RCD through diverse mediators.…”
Section: Dubs Regulating Diverse Rcdmentioning
confidence: 99%